Director's report of research in Kansas 2009 - Kansas State University. Agricultural Experiment Station (Kansas Agricultural Experiment Station Research Reports, 2010)
This report contains the title, author, and publication information for manuscripts published by station scientists.
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects